Robustness and resilience of different solid-liquid separation technologies for tertiary phosphorus removal to low levels by coagulation - Murujew, Olga; Wilson, Andrea; Vale, Peter C. J.; Bajón Fernández, Yadira; Jefferson, Bruce; Pidou, Marc (Elsevier, 2025)
In this study, three tertiary solid separation technologies were assessed on their robustness and resilience against an effluent phosphorus target of <0.3 mg P/L at steady state and dynamic conditions. The ballasted flocculation system was found to be very robust at delivering the low P target. Alternatively, cloth filtration provided a more sustainable option for less strict consents of sub 0.5 mg P/L. The effluent from the membrane system was more variable but it was shown to meet the low consents even with increased phosphorus and solids content in the feed. A molar ratio of 1.37 Fe: P was shown to be sufficient to meet the P target at short contact times as with the ballasted flocculation process. It was highlighted that optimisation of up-stream flocculation can be a considerable factor for consistent performance. Overall, the study determined key attributes of the different technologies tested providing valuable insights for technology selection at full scale.
Keywords: 4004 Chemical Engineering; 40 Engineering; Ballast; Cloth; Coagulation; Membrane; Phosphorus; Sand filter; Environmental Sciences